2020
DOI: 10.1111/iwj.13337
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of topical silicone gel in scar management: A systematic review and meta‐analysis of randomised controlled trials

Abstract: To assess the efficacy of topical silicone gel in the management of scars, we conducted this meta‐analysis. The systematic search was performed on PubMed, Web of Science and Embase, and six randomised controlled trials with a total of 375 patients were involved. The outcome data of Vancouver Scar Scale were extracted from the studies and their effect sizes were calculated using Review Manager 5.3. As a result, topical silicone gel significantly reduced pigmentation, height, and pliability scores postoperativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…12,14 Fortunately, silicone gel has been proven to be as effective as silicone sheets, allowing for easier and less obvious application. 15 This treatment can be used proactively, especially in those prone to hypertrophic scarring. 15 Botulinum toxin injections may also be utilized as a therapeutic or preventative strategy.…”
Section: Superficial Defects Hypertrophic Scarsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,14 Fortunately, silicone gel has been proven to be as effective as silicone sheets, allowing for easier and less obvious application. 15 This treatment can be used proactively, especially in those prone to hypertrophic scarring. 15 Botulinum toxin injections may also be utilized as a therapeutic or preventative strategy.…”
Section: Superficial Defects Hypertrophic Scarsmentioning
confidence: 99%
“…15 This treatment can be used proactively, especially in those prone to hypertrophic scarring. 15 Botulinum toxin injections may also be utilized as a therapeutic or preventative strategy. 12,16,17 In controlled prospective studies by Xiao et al and Elhefnawy, botulinum toxin injections into hypertrophic scars led to some level of scar improvement in 100% of their population.…”
Section: Superficial Defects Hypertrophic Scarsmentioning
confidence: 99%
“…One similar RCT 25 reported that topical silicone gel plus herbal extract gel (Allium cepa, Centella asiatica, Aloe vera, and paper mulberry) had better vascularity and pigmentation than silicone gel. Although topical silicone gel beneficial for scar prevention has been concluded by two meta-analyses with weak evidence, 26,27 the performance of topical silicone gel and other non-silicone topical treatment is also similar. 27 Thus, OE in silicone gel seems an optimal choice for scar treatment, but still needs more studies to strength this evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Although topical silicone gel beneficial for scar prevention has been concluded by two meta-analyses with weak evidence, 26,27 the performance of topical silicone gel and other non-silicone topical treatment is also similar. 27 Thus, OE in silicone gel seems an optimal choice for scar treatment, but still needs more studies to strength this evidence.…”
Section: Discussionmentioning
confidence: 99%
“…[3,4] The pathophysiology of hypertrophic scars and keloids is extremely complex, and the current therapies, such as topical formulations (silicone gel, flavonoids: onion extraction), laser treatment, corticosteroid injections and cryotherapy, are far from sufficient. [5,6] Some recent research has focused on the renin-angiotensin system (RAS) in the process of both wound healing and scar formation as a promising therapeutic target. [7] Here, we summarize and review the role of the RAS in scar formation as well as the application of these advances in the treatment of hypertrophic scars and keloids.…”
mentioning
confidence: 99%